FLOTASI DALAM PENELITIAN ARKEOLOGI - Fajari, Nia Marniati Etie (Naditira Widya, 2009)
In archaeological research, floatation is often employed to seek for plant remains, since it provides appropriate sample for palaeo-bdtany analysis. Results of such analysis may perform as reference to reconstruct the environment in the past, diet and plants benefited for human's subsistence. Nevertheless, floatation is also used to collect micro-artefacts missed by ordinary eyes. This article discusses the purpose and steps of employing floatation method, and its prospect for archaeological researches in Indonesia.